Oxidation of para-Methoxy Benzaldehyde and salicylaldehyde by N-Sadio-N-Chlorotouene Sulphonamide (Chloramine-T) in acid Medium: A Kinetic and Mechanistic Study - Venkatachalapathy, R.; Veerabhadraswamy, M.; Rangaswami (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of para-methoxy benzaldehyde and salicylaldehyde by chloramine-T (CAT) have been investigated in hydrochloric acid medium at 303 K. The rate shows first order dependence on [CAT] and fractional order in [aldehyde]. The rate increases with increase in [HCl] and shows first order dependence on [H+] and [Cl- ] variation of ionic strength. addition of reaction product (para-toluene sulphonamide) and change in dielectric constant of the medium had no significant effect on the reaction rate. Thermodynamic parameters are evaluated.